Investigating Cortical Buffering Effects of Acute Moderate Intensity Exercise: A cTBS Study Targeting the Left Dorsolateral Prefrontal Cortex - Manocchio, Felicia; Lowe, Cassandra J. (Frontiers in Human Neuroscience, 2021)
Background: The beneficial effects of both single-session bouts of aerobic exercise and therapeutic exercise interventions on the cortical regions associated with top-down attentional control (i.e., prefrontal cortex (PFC)) have been well documented. However, it remains unclear whether aerobic exercise can be used to buffer against suppressive influences on the dlPFC. Objective: The current study sought to determine whether a single session of moderate intensity aerobic exercise can offset the expected suppressive effects of continuous theta burst stimulation (cTBS) targeting the dorsolateral prefrontal cortex (dlPFC). Methods: Twenty-two right-handed participants between 19-30 years completed a 20 minute movement-only control session (10% heart rate reserve (HRR)) and moderate intensity (50% HRR) exercise in a counterbalanced order. Following each exercise session, participants received active cTBS to the left dlPFC. Changes in executive functions were quantified using a flanker paradigm employed at baseline, post-exercise and post-cTBS time points. Additionally, EEG was used to measure changes in event-related potential components related to inhibitory control (i.e., N2) and attentional control (i.e., P3) during the flanker task. Results: Behavioural results from the flanker task revealed a significant improvement in task performance following an acute bout of moderate intensity exercise. Furthermore, the effect of cTBS in both the movement-only control and moderate intensity conditions were non-significant. Similarly, EEG data from P3 and N2 ERP components revealed no changes to amplitude across time and condition. P3 latency data revealed a significant effect of time in the movement-only control condition, such that latency was shorter following cTBS. Similarly, latency data within the N2 ERP component revealed a significant effect of time on congruent trials in the movement-only control condition; N2 latency was shorter following cTBS. Conclusion: The current study revealed that light and moderate intensity exercise may provide a buffer to cTBS- induced attenuation of the dlPFC. This study provides empirical and theoretical implications on the potential for exercise to promote cognitive control.